2019
DOI: 10.1093/mnras/stz1325
|View full text |Cite
|
Sign up to set email alerts
|

A broad-band spectro-polarimetric view of the NVSS rotation measure catalogue – I. Breaking the nπ-ambiguity

Abstract: The NRAO VLA Sky Survey (NVSS) Rotation Measure (RM) catalogue is invaluable for the study of cosmic magnetism. However, the RM values reported in it can be affected by nπ-ambiguity, resulting in deviations of the reported RM from the true values by multiples of ±652.9 rad m −2 . We therefore set off to observationally constrain the fraction of sources in the RM catalogue affected by this ambiguity. New broadband spectro-polarimetric observations were performed with the Karl G. Jansky Very Large Array (VLA) at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 84 publications
(131 reference statements)
0
22
0
Order By: Relevance
“…Using the NVSS RM catalogue, Hammond et al (2012) found a similar trend-an anticorrelation between RRM variance and fractional polarisation (their Figure 19). However, as recently shown by Ma et al (2019aMa et al ( ), (2019b towards lower fractional polarisation ( 1.4 GHz 1%), the NVSS RM catalogue may be contaminated by off-axis leakage effects, which introduces extra RM uncertainties of about 13.5 rad m −2 (see Ma et al 2019b). Nevertheless, when taking only sources with 1.4 GHz 2%, a similar ∼60% decrease in RRM variance is visible in Figure 19 of Hammond et al (2012), from ∼25 to ∼ 10 rad m −2 .…”
Section: Rrm/polarisation Fraction Relationmentioning
confidence: 89%
See 1 more Smart Citation
“…Using the NVSS RM catalogue, Hammond et al (2012) found a similar trend-an anticorrelation between RRM variance and fractional polarisation (their Figure 19). However, as recently shown by Ma et al (2019aMa et al ( ), (2019b towards lower fractional polarisation ( 1.4 GHz 1%), the NVSS RM catalogue may be contaminated by off-axis leakage effects, which introduces extra RM uncertainties of about 13.5 rad m −2 (see Ma et al 2019b). Nevertheless, when taking only sources with 1.4 GHz 2%, a similar ∼60% decrease in RRM variance is visible in Figure 19 of Hammond et al (2012), from ∼25 to ∼ 10 rad m −2 .…”
Section: Rrm/polarisation Fraction Relationmentioning
confidence: 89%
“…However, these previous all-sky polarisation surveysprincipally the catalogue of Taylor, Stil, & Sunstrum (2009), produced from the National Radio Astronomy Observatory (NRAO) Very Large Array (VLA) Sky Survey (NVSS; Condon et al 1998)-contain large systematic uncertainties, due to their poor frequency sampling (e.g., Van Eck et al 2011;Ma et al 2019a). However, next-generation surveys (such as POSSUM and the Karl G. Jansky Very Large Array Sky Survey; Lacy et al 2020) possess large fractional bandwidths that are finely sampled in frequency, which mitigates many of the systematic uncertainties of the Taylor et al (2009) catalogue.…”
Section: Introductionmentioning
confidence: 99%
“…Upon comparison between our derived FD new and their listed FD TSS09 (Figure 2 top panel), we found that 32 out of the 85 sources (almost 40 per cent) have the two values differ by more than 500 rad m −2 . This is most likely due to the nπ-ambiguity issue of the Taylor et al (2009) catalogue (see Ma et al 2019a). Furthermore, we noted two sources (NVSS J183220−103510 and NVSS J183409−071802) that, despite being listed as polarised in the Taylor et al (2009) catalogue at 1.01 ± 0.05 and 0.85 ± 0.02 per cent, respectively, were unpolarised in our new VLA observations (with p new lower than 6σ cutoffs of 0.24 and 0.12 per cent, respectively).…”
Section: Comparisons With Existing Faraday Depth Measurementsmentioning
confidence: 99%
“…Faraday thick sources would also invalidate our assumptions, and we assume that there are none in our data as Faraday thickness can be consistent with a two-component model depending on the wavelength sampling (e.g. Ma et al 2019;Brentjens & de Bruyn 2005). Nevertheless some external Faraday dispersion would be covered by our model, as depending on observing parameters Faraday thick sources may appear as two screens (Van Eck et al 2017).…”
Section: Assumptions On Faraday Dispersion Functionsmentioning
confidence: 84%